2020
DOI: 10.1103/physreva.102.063522
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of boosted terahertz radiation from air plasma pumped by a femtosecond three-color sawtooth field

Abstract: We report on the coherent control of boosted ultrashort terahertz pulse emitted from air plasma pumped by a femtosecond sawtooth pulse composed of three optical harmonic fields. With an in-line optical setup, the relative phases between the three optical components of the pump pulse can be varied independently with attosecond precision without the complexity of external phase stabilization. We observe that the amplitude of the terahertz emission pumped by the phase-optimized sawtooth wave is enhanced by 1.8 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This period doubling originates from breaking the mirror symmetry of the two color fields containing only the fundamental and second harmonics due to the addition of the third harmonic. This effect is very similar to the period doubling that occurs in the phase dependence of the amplitude of THz radiation generated by the three-color pulse [18].…”
supporting
confidence: 55%
See 2 more Smart Citations
“…This period doubling originates from breaking the mirror symmetry of the two color fields containing only the fundamental and second harmonics due to the addition of the third harmonic. This effect is very similar to the period doubling that occurs in the phase dependence of the amplitude of THz radiation generated by the three-color pulse [18].…”
supporting
confidence: 55%
“…Moreover, it has been demonstrated that ionization of molecules can be enhanced and coherently controlled with two-color laser pulses composed of a fundamental frequency with either its second or third harmonics [13][14][15]. Recently, it has been reported that a laser field composed of 3 or more colors can be even more beneficial [16][17][18]. Compared to two-color laser field excitation, the three-color scheme provides extra control parameters and has proven its versatility in the selection of single harmonic radiation from the comb of high-order harmonics [19], in the coherent control of the polarization and chirality of THz pulses produced from air plasma [18], and in the generation of supercontinuum ranging from mid-infrared to ultraviolet [17,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step towards more complex pulses, we consider a trichromatic application. Trichromatic fields offer enhanced possibilities for ultrafast applications such as multicolor spectroscopy [214], strong-field physics [215,216], the generation of terahertz radiation [217,218] and HHG [219]. Further examples of trichromatic pulse sequences are illustrated in Figure 12.…”
Section: Multichromatic Pulse Sequencesmentioning
confidence: 99%
“…This can be done using the frequency tuning of the ionizing pulse components in optical parametric generators [11][12][13]. Recently, the possibility of using multi-color (three or more) pulses instead of traditional two-color ionizing pulses has been increasingly investigated [13][14][15][16]. The solution of optimization problems for such systems is complicated by the fact that the extremely nonlinear nature of ionization-induced multiwave mixing (IMWM) manifests itself in a strong interdependence of the optimal values of each pulse parameter on the values of all others [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%